School counselling with families at psychosocial risk: analysis of educational alliance with kinship foster care - García-Bermejo, Tania; Fuentes, Juan Luis (Revista Complutense de Educación, 2023)
This article analyses the possibilities of creation of educational alliance in schools with families in psycho-social risk and, more specifically, with kinship foster care. Based on four dimensions of the System for Observing Family Therapy Alliances, it focus on the necessary engagement for which kinship caregivers and children feel recognized and welcomed, and stay in it; safety in the system, that allows the family trust in the counsellor and find in the common conversation an open and accessible space; emotional connection, that makes the family feel respected, valued and comprehended by the professional, who trust in their capabilities; and a shared feeling of purpose in the family, for what all the members conceive the orientation as a common issue that motivate to act, providing valuable resources for the success of intervention.